Human Immunodeficiency Virus-1 Diversity in the Moscow Region, Russia: Phylodynamics of the Most Common Subtypes - Lebedev, Aleksey; Lebedeva, Natalya; Moskaleychik, Fedor; Pronin, Alexander; Kazennova, Elena; Bobkova, Marina (Frontiers in Microbiology, 2019)
This study analyzes the HIV-1 subtype diversity and its phylodynamics in Moscow region, which is the most densely populated area of Russia characterized by high rates of internal and external migration. The demographic and viral data from 896 HIV-infected individuals collected during 2011-2016 were analyzed. The study revealed broad diversity in the HIV-1 subtypes found in Moscow, which included A6 (85.1%), B (7.6%), CRF02_AG (1.2%) and URF_A6/B recombinants (4.2%). Other HIV-1 subtypes were detected as single cases. While A6 was most prevalent (> 86.0%) among heterosexuals, injecting drug users and cases of mother-to-child transmission of HIV, subtype B (76.3%) was more common in men who have sex with men. Phylogenetic reconstruction revealed that the A6 sequences were introduced into the epidemic cluster that arose approximately around 1998. Within the subtype B, six major epidemic clusters were identified, each of which contained strains associated with only one or two dominant transmission routes. The date of origin of these clusters varied between 1980 and 1993, indicating that the HIV-1 B epidemic began much earlier than the HIV-1 A6 epidemic. Reconstruction of the demographic history of subtypes A6 and B identified at least two epidemic growth phases, which included an initial phase of exponential growth followed by a decline in the mid/late 2010s. Thus, our results indicate an increase in HIV-1 genetic diversity in Moscow region. They also help in understanding the HIV-1 temporal dynamics as well as the genetic relationships between its circulating strains.